肺高血圧症の処置のためのトレプロスチニル (2025)
本発明は、肺高血圧症と診断されているか、または肺高血圧症を発症するリスクがある対象における肺高血圧症を処置する方法で使用するためのトレプロスチニルまたはその薬学的に許容可能な塩もしくは誘導体を提供し、処置は、ｉ）第１の処置期間の間、エアロゾル化形態で第１の濃度のトレプロスチニルまたはその薬学的に許容可能な塩もしくは誘導体を含む第１の液体組成物を前記対象に投与する工程と、ｉｉ）第１の処置期間の後の第２の処置期間の間、エアロゾル化形態で第２の濃度のトレプロスチニルまたはその薬学的に許容可能な塩もしくは誘導体を含む第２の液体組成物を前記対象に投与する工程と、を含み、第２の液体組成物中のトレプロスチニルまたはその薬学的に許容可能な塩もしくは誘導体の第２の濃度は、第１の液体組成物中のトレプロスチニルまたはその薬学的に許容可能な塩もしくは誘導体の第１の濃度よりも高く、第１および第２の液体組成物は、エアロゾル化され、ソフトミスト吸入器を使用して対象に投与される。【選択図】図１ The invention provides Treprostinil or a pharmaceutically acceptable salt or derivative thereof for use in a method of treatment of pulmonary hypertension in a subject being diagnosed with pulmonary hypertension or being at risk of developing pulmonary hypertension wherein the treatment comprises the steps of i) administering to said subject a first liquid composition comprising Treprostinil or a pharmaceutically acceptable salt or derivative thereof in a first concentration in aerosolized form for a first treatment period, and ii) administering to said subject a second liquid composition comprising Treprostinil or a pharmaceutically acceptable salt or derivative thereof in a second concentration in aerosolized form for a second treatment period following the first treatment period; wherein the second concentration of Treprostinil or a pharmaceutically acceptable salt or derivative thereof in the second liquid composition is higher than the first concentration of Treprostinil or a pharmaceutically acceptable salt or derivative thereof in the first liquid composition, and wherein the first and the second liquid compositions are aerosolized and administered to the subject using a soft mist inhaler.